(untitled) (ЕтноАнтропоЗум, 2011)
This paper talks about the beliefs of the potters from the Chernigov region in the Ukraine. Namely, when the potters prepared the pottery, traditionally they included a plethora of magic activities in order to control the elements directly involved in the process. Candles had a significant role during these magic rituals and this is considered a preChristian feature dedicated to the cult of the old Slavic God Perun.